STRATEGI PEMASARAN USAHA MIKRO KECIL MENENGAH DALAM MENINGKATKAN DAYA SAING (STUDI KASUS WARUNG KOPI DOTTORO JALAN TINUMBU MAKASSAR) - Najib, Marhawati; Fuad, M. Fikri Nur; Mustari; Rahmatullah; Tadampali, Andi Caezar To (IAIN Ambon, 2024)
Marketing strategies are essential to apply in all areas related to business. Without marketing, the business you run will not develop rapidly. This research aims to determine the marketing strategy carried out by the Dottoro coffee shop business to increase sales. This research is descriptive research using a qualitative approach. The informant was chosen deliberately, namely the owner of the Dottoro coffee shop. Data collection procedures used in research include observation, interviews, and documentation. The data obtained was analyzed using SWOT analysis. Based on the research results, show that the strategy implemented by the Dottoro coffee shop business in Jalan Tinumbu Makassar, South Sulawesi Province is in quadrant one, namely Aggressive (growth-oriented strategy), which is a very profitable situation with implementation through Marketing Strategy. The coordinates of point x are the IFAS strategy coordinates with a coordinate point obtained, namely 3.45. In contrast, the coordinates of point y are the coordinates of the EFAS strategy with a coordinate point obtained, namely 3.06. The strategy that needs to be improved in the coffee shop business is to maintain the reputation of the Dottoro coffee shop by serving local specialty coffee. The availability of raw materials will make it easier for the Dottoro Coffee Shop business to expand locations in strategic places. Keywords: Coffee shop, marketing strategy, SWOT analysis, MSMEs